Value Creation Induces and their influence on Market Value: Case of agro-industrial companies that are part of IGBVL, 2009-2018 - Díaz Bazán, Bladimiro (2022)
The present work sought to determine the significant influence of the Inducers of Value Creation (ICV) in the Market Value of Own Capital (VMCP) of the agro-industrial companies that are part of the General Index of the Lima Stock Exchange (IGBVL): Alicorp, Casagrande and Pomalca, and propose a linear financial model that helps its executives to promote a culture of business management based on value creation. For this purpose, as we have worked previously (B. Díaz, 2020), the average quarterly value of the VMCP indicator (variable explained) was estimated and the accounting accounts of he Financial Statements of the period 2009-2018 were conventionally regrouped, estimating the values of the ICV (explanatory variable), then we applied the statistical process and the linear regression study (R2). The financial information showed for Alicorp and Pomalca a joint explanatory capacity of the growth inducers on their VMCP of 69% and 80% and of those of profitability of 34% and 29%, respectively; for Pomalca, also those with competitive advantage explained 23% and for Casagrande only the inducers of Profitability evidenced explanatory power of 25%. Finally, the joint explanatory power of the inducers of value creation with the VMCP was 68% in the case of Alicorp, 43% of Casagrande and 84% of Pomalca.